2016
DOI: 10.18632/oncotarget.14119
|View full text |Cite
|
Sign up to set email alerts
|

Use of non-selective β-blockers is associated with decreased tumor proliferative indices in early stage breast cancer

Abstract: Previous studies suggest beta-adrenergic receptor (β-AR) antagonists (β-blockers) decrease breast cancer progression, tumor metastasis, and patient mortality; however the mechanism for this is unknown. Immunohistochemical analysis of normal and malignant breast tissue revealed overexpression of β1-AR and β3-AR in breast cancer. A retrospective cross-sectional study of 404 breast cancer patients was performed to determine the effect of β-blocker usage on tumor proliferation. Our analysis revealed that non-selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
103
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(111 citation statements)
references
References 54 publications
6
103
2
Order By: Relevance
“…However, propranolol (a non-selective β-blocker) was identified to be effective in treating severe infantile hemangiomas and has been approved as the first-line therapy for proliferating infantile hemangioma by the US Food and Drug Administration in 2014 (16). A number of in vitro and in vivo studies have also demonstrated the antitumor activity of β-blockers against various types of cancer, including breast (17,18), pancreatic (19) and prostate cancer (20), and ovarian carcinomas (21), melanoma (22) and neuroblastoma (23). Işeri et al (24) identified that propranolol and ICI 118,551 (selective β 2 -blockers) inhibited the invasion and migration of non-stimulated breast cancer cells (MCF-7) in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…However, propranolol (a non-selective β-blocker) was identified to be effective in treating severe infantile hemangiomas and has been approved as the first-line therapy for proliferating infantile hemangioma by the US Food and Drug Administration in 2014 (16). A number of in vitro and in vivo studies have also demonstrated the antitumor activity of β-blockers against various types of cancer, including breast (17,18), pancreatic (19) and prostate cancer (20), and ovarian carcinomas (21), melanoma (22) and neuroblastoma (23). Işeri et al (24) identified that propranolol and ICI 118,551 (selective β 2 -blockers) inhibited the invasion and migration of non-stimulated breast cancer cells (MCF-7) in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Montoya et al [100] demonstrated that selective β 1 -adrenoceptor antagonist therapies were less effective against proliferation of tumors than nonselective ones. The above lines of evidence, in a simplistic interpretation, may be explained in 2 main ways: (1) it is mandatory to induce the blockade of more than one β-adrenoceptor type, and/or (2) β 1 -adrenoceptor blockade alone is not responsible for the therapeutic effects in these cases.…”
Section: Main Side Effects Resulting From β-Adrenoceptor Blockadementioning
confidence: 98%
“…A single ER+, HER2− patient was treated with 25 days of propranolol 1.5 mg/kg per day after diagnostic biopsy but before resection. Resection of tumor tissue showed a 23% reduction in Ki67 staining compared to biopsy tissue 25 days earlier, before any propranolol 185. Of important note, beta-1-selective beta-blockers did not work to reduce Ki67, only nonselective beta-blockers did.…”
Section: Drugs To Inhibit Emtmentioning
confidence: 86%